EFEKTIFITAS NURSING TELEHEALTH DALAM MEMBERIKAN ASUHAN AKEPERAWATAN: EFEKTIFITAS NURSING TELEHEALTH DALAM MEMBERIKAN ASUHAN AKEPERAWATAN - Hasibuan, Anisah Khayrani; NURHIDAYAH, RIKA ENDAH (Universitas Aufa Royhan, 2023)
Nursing Telehealth has a very effective impact on nurses in providing nursing services. The use of increasingly sophisticated media can penetrate the barrier between nurses and patients. Referring to Florence Nightingale's nursing paradigm, modern nursing theory was developed to describe the interaction between nursing, patient environment, health, and individual basic needs. The use of information and communication technology has impacted the evolving role of nursing in modern healthcare systems that have embraced the whole setting. Besides the many benefits, Nursing Telehealth must be faced with the readiness of human resources, financing, facilities and infrastructure as well as clear legal aspects. The purpose of this literature review is to describe the use of Telehealth in the nursing profession to provide professional care. Method: research design using Literature Review, based on summaries of several studies related to the Nursing Telehealth research topic. The journal can be accessed by searching the ProQuest database and Google Scholar 2019-2023. Results: Based on the journals collected, the use of Nursing Telehealth in nursing care can increase the effectiveness of nursing care services. Conclusions and Recommendations: Nursing Telehealth is effective in facilitating nurses in carrying out professional and effective nursing care and shortening the time and distance of services. The author recommends that Nursing Telehealth be implemented in Indonesia in stages considering Indonesia's geographical conditions.